(untitled) (Journal of Science and Engineering, 2026)
A retaining wall is a structure designed to resist the lateral pressure exerted by soil, water, or both, especially where elevated soil needs support above stable ground. For low heights, gravity retaining walls are commonly used, relying on their own weight for stability. However, as wall height increases, gravity walls become uneconomical due to the large size and volume of materials required. For medium heights, cantilever retaining walls—typically L- or inverted T-shaped—offer better material efficiency, with thinner stems supported by a base slab. Yet, they become risky for higher walls, as minor foundation defects or scouring at the toe can lead to structural failure and an uneconomical design. In such cases, counterfort retaining walls are preferred. These walls use vertical supports (counterforts) placed at regular intervals on the soil-facing side to reduce bending moments and increase stability. Though effective for tall walls, counterfort designs are complex, labor-intensive, and require skilled workmanship. This paper presents a new type of retaining wall that has been developed by combining the principles of both gravity and cantilever designs. It consists of parallel double walls connected by tie members, spaced vertically at regular intervals. Three-dimensional analysis shows a significant reduction in stress, making this design more economical and safer. Additionally, it does not require skilled labor and allows for faster construction than counterfort walls.